2023
DOI: 10.1002/cbm.2289
|View full text |Cite
|
Sign up to set email alerts
|

Towards more accurate classification of risk of arrest among offenders on community supervision: An application of machine learning versus logistic regression

Abstract: Background: Although there is general consensus about the behavioural, clinical and sociodemographic variables that are risk factors for reoffending, optimal statistical modelling of these variables is less clear. Machine learning techniques offer an approach that may provide greater accuracy than traditional methods. Aim: To compare the performance of advanced machine learning techniques (classification trees and random forests) to logistic regression in classifying correlates of rearrest among adult probatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…A classification tree approach to violence risk assessment exists, albeit validated in a general psychiatric patient sample (Monahan et al., 2000) and may be more widely implemented in the context of digital technology advances in clinical practice. More recently, it has been further demonstrated that machine learning techniques possess significantly greater accuracy when correlated with rearrest (Maynard et al., CBMH this issue).…”
Section: Needs For Digital Technology In Forensic Psychiatrymentioning
confidence: 99%
See 1 more Smart Citation
“…A classification tree approach to violence risk assessment exists, albeit validated in a general psychiatric patient sample (Monahan et al., 2000) and may be more widely implemented in the context of digital technology advances in clinical practice. More recently, it has been further demonstrated that machine learning techniques possess significantly greater accuracy when correlated with rearrest (Maynard et al., CBMH this issue).…”
Section: Needs For Digital Technology In Forensic Psychiatrymentioning
confidence: 99%
“…Digital technology is being explored to as a way of improving identification of indicators of relapse of escalating risk (see Maynard et al., this issue). An early attempt to introduce Iterative Classification Trees into clinical practice was promising (Monahan et al., 2000) and might now be revisited as everyday clinical access to digital technology is so improved.…”
Section: Into the Futurementioning
confidence: 99%